Upgrade to DIII-D National Fusion Facility PCS and Neutral Beam Systems: In-Shot Variation of Neutral Beam Particle Energy. (3rd October 2017) - Rauch, J.; Pace, D. C.; Crowley, B.; Johnson, R. D.; Kellman, D. H.; Pawley, C. J.; Scoville, J. T.
Abstract: On the DIII-D National Fusion Facility tokamak plasma diagnostics continue to improve and experiments increase in complexity. Hence the utility of dynamic control of the beam energy (and therefore also the injected torque, ion heating fraction, etc.) has become apparent. Here we report on upgrades that have been incorporated into the DIII-D Plasma Control System (PCS) and Neutral Beam Injection (NBI) systems in order to allow the beam acceleration voltage (Vaccel) to be varied continuously in a ≤20 kV range during a shot for the first time, generating new capabilities such as smooth plasma transitions and controllable interactions with Alfvén waves.